Assessing Patient Satisfaction in Public Healthcare: The Impact of Professional Relationships, Skills, and Facility Amenities - Nusrah Samat; Hemarubini R Paramasivam; Fatimah, Siti; Noor Fzlinda Fabeil (PROFESSIONAL HEALTH JOURNAL, 2024)
Introduction: Public healthcare services play an essential role in providing health facilities or services for citizens who seek fundamental medical services. Patients’ satisfaction with healthcare services is mainstream as they are the service consumers. Therefore, it reflects how effective the services that have been given by the health care provider are. Objectives: to investigate the influence of relationships and interaction with healthcare professionals, perception of healthcare professional skills, amenities, and registration and administrative procedures towards patient satisfaction. Methods: A total of 160 sets of questionnaires received from the respondent of purposive sampling through the online survey that was analyzed with descriptive and inferential technique of correlation, and regression.Results: The relationship and interaction with healthcare professionals (β = 0.281, p < 0.01), perception of healthcare professionals' skills (β = 0.396, p < 0.01), registration and administration process (β = 0.117, p < 0.01), and evaluation of amenities, accessibility, and facilities (β = 0.164, p < 0.01) were all significant predictors of patient satisfaction. Conclusions: By prioritizing the development of strong professional relationships, improving perceived skills of healthcare providers, optimizing administrative processes, and upgrading facility amenities, healthcare providers and policymakers can foster environments where patient satisfaction and overall healthcare quality thrive.